Space Making for Collective Well-being: Design, Dynamics, and Implications - dian nafiatul awaliyah (Advances in Civil Engineering and Sustainable Architecture, 2024)
This paper explores the multifaceted concept of space making for the collective well-being across diverse disciplines and contexts. Drawing on discussions regarding collaboration facilitation, narrative transformation, diverse approaches to space design, challenges, and opportunities, as well as inclusivity and equity considerations, it delves into the complexities of creating environments that foster collaboration, inclusivity, and equity. The research question addresses how various approaches to space making contribute to collective well-being, encompassing collaboration facilitation, narrative transformation, diverse design perspectives, challenges, and opportunities, as well as inclusivity and equity considerations. The objective is to analyze these discussions to gain insights into the dynamics of space making for collective well-being. Qualitative methods are employed to analyze discussions and findings across different disciplines. The findings highlight the importance of fostering collaboration, challenging existing narratives, utilizing diverse approaches, addressing challenges, and promoting inclusivity and equity in space making for collective well-being. The paper underscores the significance of creating spaces that promote collaboration, inclusivity, and equity in shaping a more just and thriving collective future.